2004
DOI: 10.1002/bjs.4718
|View full text |Cite
|
Sign up to set email alerts
|

Germline RET V804M mutation associated with multiple endocrine neoplasia type 2A

Abstract: Rare mutation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
1
18
0
1
Order By: Relevance
“…In contrast, heterozygous point mutations in codon 804 leading to a substitution of valine 804 by either leucine (V804L) or methionine (V804M) have been reported in several families with FMTC (22)(23)(24), while MEN-2A was very rarely observed. To our best knowledge, before our case, only Gibelin et al (9) reported a family in which a V804M mutation was associated to MEN-2A (MTC plus hyperparathyroidism) in one member. Thus, assuming that MEN-2A phenotype is a rare expression of V804M mutation, the high frequency of 804 codon mutations in Sardinia could also explain the reason why we also observed a patient with a MEN-2A phenotype.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, heterozygous point mutations in codon 804 leading to a substitution of valine 804 by either leucine (V804L) or methionine (V804M) have been reported in several families with FMTC (22)(23)(24), while MEN-2A was very rarely observed. To our best knowledge, before our case, only Gibelin et al (9) reported a family in which a V804M mutation was associated to MEN-2A (MTC plus hyperparathyroidism) in one member. Thus, assuming that MEN-2A phenotype is a rare expression of V804M mutation, the high frequency of 804 codon mutations in Sardinia could also explain the reason why we also observed a patient with a MEN-2A phenotype.…”
Section: Discussionmentioning
confidence: 75%
“…The disease in these individuals tend to be aggressive as evidenced by regional lymph node involvement in approximately 90% of macrocarcinomas and up to 30% microcarcinomas (65). (69). A comparative analysis of clinical, biochemical and histopathological features was performed by Niccoli-Sire et al in 2001 between FMTC index cases harboring non-cysteine (exons 13-15) and cysteine RET mutations (exon 10) (47).…”
Section: Phenotype Expression: Cysteine Versus Non-cysteine Mutationsmentioning
confidence: 99%
“…In contrast to majority of RET 804 (non-cysteine) mutation carriers who remain biochemically normal till the third decade of life (54), individuals with classical cysteine mutations (codon 634) show a positive pentagastrin test during the first decade of life (6,(62)(63)(64). Additional studies have also described HPTH in association with V804M (50,59,69,99) and V804L mutations (58,60). Their results differed from earlier findings in that the authors found no statistically significant difference between the groups in mean age at diagnosis and stage of C-cell disease including size of MTC (macroscopic or microscopic), bilaterality, presence of CCH and regional node involvement.…”
Section: Phenotype Expression: Cysteine Versus Non-cysteine Mutationsmentioning
confidence: 99%
“…Finally, total agreement was also expressed regarding the ATA-R #15 which indicates to treat MEN 2B patients harboring codon 804 mutation associated to another mutation similarly to those with the more typical MEN 2B RET causing mutations. Indeed, data from the literature report that the phenotype associated to V804M mutation alone is mostly FMTC [8,9], though also MEN 2A cases have been described [9-11]. However, when this mutation is associated to another on the same allele (Y806C, S904C, E805K, V778I) the phenotype resembles that of MEN 2B [12-16].…”
Section: European Comments To Ata-r 1-5 and 9-15mentioning
confidence: 99%